PALAEODEMECOLOGICAL ANALYSIS OF INFAUNAL BIVALVES “LEBENSSPUREN” FROM THE MULICHINCO FORMATION, LOWER CRETACEOUS, NEUQUÉN BASIN, ARGENTINA (Ameghiniana, 2012)
The study of palaeodemecological features requires some particular taphonomic conditions. These conditions were met in the Mulichinco Formation (Valanginian), where burrowing bivalve trace fossils are widespread and often appear in cross section on bedding surfaces. Two groups of such beds were analyzed, measuring population density, spatial distribution, size distribution and horizontal orientation of the burrows. The palaeoenvironment was established by means of a detailed sedimentological analysis, and the bivalve fauna present was checked, in order to attempt identifying their potential producers. High population densities were found in the two groups, indicating favourable physical conditions and good food supply, while differences in both spatial and size distributions were noticed between them; on most surfaces there was no preferred orientation. The first group (group A) showed a uniform pattern of spatial distribution and larger traces, with a remarkable absence of small sizes. In the second group (group B), the spatial distribution pattern is indistinguishable from a random distribution (except one case in which the pattern appears to be aggregated). Group A is interpreted as a set of escape traces made by deep burrowers in response to storm deposition, while group B is considered as resting/escape traces made by shallow burrowers in tide-dominated environments. Palaeodemecological studies of this kind are potentially useful tools for sedimentary and basin analyses.Resumen. ANALISIS PALEODEMECOL ÓGICO DE SIGNOS DE ACTIVIDAD DE BIVALVOS INFAUNALES DE LA FORMACIÓN MULICHINCO , CRETÁCICO INFERIOR , CUENCA NEUQUINA , ARGENTINA . El estudio de rasgos paleodemecológicos requiere de ciertas condiciones tafonómicas particulares. En la Formación Mulichinco (Valanginiano) se cumplen dichas condiciones, siendo frecuentes los signos de actividad de bivalvos excavadores que aparecen en sección transversal sobre las superficies de estratificación. Dos grupos de tales superficies fueron analizados, midiendo densidad poblacional, disposición espacial, distribución de tamaños y orientación en planta de las excavaciones. El paleoambiente se determinó por medio de un análisis sedimentológico detallado, y se registró la fauna de bivalvos presente con la intención de identificar a los potenciales productores. Se encontraron altas densidades poblacionales para ambos grupos, lo que indica condiciones físicas favorables y buen suministro de alimento, en tanto que la disposición espacial y la distribución de tamaños difiere entre dichos grupos; no se advirtió orientación preferencial en la mayoría de las superficies. El primer grupo (grupo A) muestra un patrón uniforme de disposición espacial y trazas de mayor tamaño; llama la atención la ausencia de pequeños tamaños. En el segundo grupo (grupo B), el patrón de disposición es indistinguible de uno al azar (salvo en un caso donde parece haber un patrón agregado). Se interpreta al grupo A como un conjunto de rastros de escape realizados por excavadores profundos en respuesta a depósitos de tormenta, en tanto que el grupo B es considerado como un conjunto de rastros de reposo/escape hechos por excavadores superficiales en ambientes dominados por mareas. Estudios paleodemecológicos de este tipo representan herramientas potencialmente útiles para los análisis sedimentológicos y de cuencas.